The Journey of the Mind Into God: On the trail of that peace which overbid all understanding (2019)
The current text collects a brief presentation of a PhD project that aims to make a philosophical approach to the Itinerarium mentis in Deum (The Journey of the Mind into God) work, written in the thirteenth century by St. Bonaventure. Also, the Latin-Castilian bilingual edition by the B.A.C., works by St. Bonaventure from 1947, will be worked through this thesis as a primary source. Furthermore, a collection of some secondary references in the literature is presented at the end of this document. Finally, the central hypothesis of the project points to the fact that contemporary man in his immanent way of understanding the world and being bent towards himself, has given a character of fundamental to what is relative, as well as forgetting his transcendent nature ignoring the dialectical relationship that leads him through the everyday experience to God.